The Effects of Project-Based Learning and Cooperative Learning Group Investigation towards Student’s Concept Mastery at SMA in Respiratory System - Sukmawati Sundari Siregar; Ely Djulia; Hasruddin Hasruddin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research aimed to investigate the effect of using project based learning (PjBL) toward student’s concept learning of exact eleven grade senior high school students in respiratory system. The design of the study was quasi-experimental research design with pre-test and post-test control group design.The population of this research was all students in exact eleven grade of SMA Medan Academic Year 2014/2015 which consist of 11 classes. Taking sample done by using purposive sampling technique and the classes chosen are three classes i.e. XI MIA 10 (PjBL), XIMIA 7 (GI) and XIMIA 5 (Conventional). Research instrument are multiple choices (C1-C6) for collecting the student’s concept mastery aspect. The statistical assumption test revealed that the data were normally distributed and homogent. Hypothesis analysed using Analysis of Covariant (ANACOVA) followed by Tukey’s test assisted by SPSS 19.00. Research result showed that learning models effect the student’s concept mastery significantly. Student’s concept mastery was 80,05± 4, 23 for project-based learning class, and it differs significantly towards group investigation class (73,75 ± 5,95) (P=0,000), and conventional class (70,77±5,56) (P=0,000). Group investigation also differs significantly towards conventional learning (P=0,023). The result showed that student’s concept mastery on project-based learning class was higher than group investigation and conventional learning class.Keywords: Project-Based Learning, Group Investigation, Concept Mastery, Scientific Attitude, Creative Thinking Skill